Patient reported experience measures: an assessment of the out-patient pharmacy in a tertiary care teaching hospital - Muneeza; Yathindra, Chitra (International Journal Of Community Medicine And Public Health, 2024)
Background: Patient Reported Experience Measures (PREMs) are essential for assessing healthcare service quality, directly reflecting patient satisfaction. This study evaluates patient experiences in an out-patient pharmacy of a tertiary care teaching hospital to identify factors influencing pharmacy service satisfaction. Methods: A cross-sectional study was conducted from August 30 to September 16, 2023, with 49 patients who used the out-patient pharmacy. Data was collected via a structured, close-ended questionnaire using a 3-point Likert scale. Analyses included frequency, percentage, mean, and standard deviation. Results: The study revealed that 46% of patients rated medicine availability as "excellent," while 8% were dissatisfied. Service timeliness received a 40% "excellent" rating, yet 32% found the overall wait unsatisfactory. Patient satisfaction with staff knowledge and assistance was high, with 55% rating it "excellent." However, billing and crowd management needed improvement, with 30% and 22% of patients rating these areas as "poor," respectively. Overall, 40% of patients were highly satisfied, while 18% expressed dissatisfaction. Conclusions: The findings highlight both strengths and areas for improvement in the out-patient pharmacy. While patients appreciated medicine availability and knowledgeable staff, service delays and billing issues were areas of concern. Regular feedback and targeted interventions are crucial to enhance pharmacy operations and patient satisfaction.